Comparative study of artemether and quinine treatment in severe and complicated falciparum malaria at Balikpapan General Hospital - Tjitra, E.; Oemijati, S.; Oey, T. S.; Pribadi, W.; Tjiptaningsih, B.; Leman, Y.; Mamesah, H.; Arbani, P. R.; Darwoto, Darwoto; Syahrudji, N.; Sudiarso, Sudiarso; Gunawan, S. (Faculty of Medicine Universitas Indonesia, 1996)
[no abstract available]